Market Revenues and Economic Opportunities in the Legal Cannabis Market in Uruguay - Rychert M; Pardal M; Queirolo R (LSE Press, 2025)
Background: The regulated cannabis market in Uruguay has received international attention as an alternative to profit-maximising cannabis legalisation models. However, relatively little is known about how this market has been operationalised. The goal of our policy commentary is to identify the key actors with a role in the legal regulated cannabis market, provide estimates of the annual revenues, discuss the existing market opportunities, and consider the implications for the economic aspects of social justice. Methods: Our commentary is informed by a review of key relevant literature and other documentary sources, as well as insights from qualitative fieldwork in Montevideo. Results: Licensed production companies and pharmacies are key for-profit organisations involved in the recreational cannabis market in Uruguay. With prices, products, and market size controlled by the government, the entrepreneurial decisions of licensed producers are limited, resulting in a focus on cost reduction. The production sector is characterised by a small number of companies that operate at economies of scale, illustrating a ‘commoditised’ cannabis market model. The pharmacy-only retail framework has created new revenue for community pharmacists but may hinder the participation of small-scale legacy players. The not-for-profit Cannabis Social Club (CSC) sector has lower entry barriers and fewer requirements regarding products and prices, but only a few key individuals may benefit financially due to the sector non-profit regulation. Estimates of annual revenues in the licensed production (4–4.8 million USD), pharmacy point-of-sale (1.1–2.2 million USD) and CSC sectors (8–17.7 million USD) are provided. Conclusions: Despite not being designed to pursue economic objectives, the state-controlled cannabis market in Uruguay has created commercial opportunities for several actors. Our analysis suggests that this regulation may represent a compromise from an economic and social justice perspective.
Keywords: cannabis industry; legalisation; government monopoly; cannabis retail; non-profit; market